Research, Design FPGA Practical Kit - Nguyễn Đình Phú; Trương Thị Bích Ngà; Phan Vân Hoàn (Journal of Technical Education Science, 2024)
Various imported FPGA kits have been used for teaching digital circuit design in practical labs at the University of Technical and Education in Ho Chi Minh City since 2008. Many damaged kits cannot be repaired once broken while in service and must be replaced with others, causing considerable waste-replacement with different FPGA kits results in equipment and learning materials discrepancies. The designs of some of the kits need to be optimized to mitigate teaching and learning difficulties. This paper analyzes the advantages and limitations of used FPGA kits using analytical and experimental methods to propose a new FPGA kit design. The new kit is designed with many peripherals suitable for the duration of a single course; the peripherals are designed independently, the communication circuits choose the correct logic level, and the components utilized in the kit's design must guarantee optimal durability, uncomplicated upgrade and easy replicability.